Facile and scalable synthesis of Ti₅Si₃ nanoparticles via solid-state route in an autoclave - Mao, W.; Bao, K.; Cao, F.; Ye, L.; Xie, H.; Li, B.; Wang, W. (Сверхтвердые материалы, 2017)
A novel method of the synthesis of titanium silicide nanoparticles via solid-state route in an autoclave at 700 °C is reported. The reaction of titanium silicide could be described briefly as: 5TiO₂ + 3Si + 20Li = Ti₅Si₃ + 10Li₂O. XRD pattern indicated that the product was hexagonal Ti₅Si₃. The Ti₅Si₃ particle size (about 20–40 nm) is confirmed by the TEM images. Furthermore, the thermal stability and oxidation resistance of the titanium silicide nanoparticles were also investigated. Повідомлено про новий метод синтезу наночастинок силіциду титану твердотільним шляхом в автоклаві при температурі 700 °С. Реакція силіциду титану може бути коротко записана як 5TiO₂ + 3Si + 20Li = Ti₅Si₃ + 10Li₂O. XRD-зображення показало, що продукт є гексагональним Ti₅Si₃. Розмір частинок Ti₅Si₃ (∼ 20–40 нм) підтверджено ПЕМ-зображенням. Також досліджено термостабільність і опір окисленню частинок силіциду титану. Сообщается о новом методе синтеза наночастиц силицида титана твердотельным путем в автоклаве при температуре 700 °С. Реакция силицида титана может быть кратко записана как 5TiO₂ + 3Si + 20Li = Ti₅Si₃ + 10Li₂O. XRD-изображение показало, что продукт является гексагональным Ti₅Si₃. Размер частиц Ti₅Si₃ (∼ 20–40 нм) подтвержден ПЭМ-изображением. Также исследованы термостабильность и сопротивление окислению частиц силицида титана.